PENINGKATAN HAFALAN AL-QUR'AN MELALUI METODE TALAQQI - Ilmi Rosyidatul; S` Suhadi; Mukhlis Faturrohman (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
The purpose of this study was to determine the implementation of the talaqqi method of learning tahfidzul Qur'an. This research is descriptive qualitative. The subject of this research is MI Al-Islam Grobagan Surakarta. Observations, interviews, and documentation are tools for data collection. While the data analysis technique uses data redaction, data presentation, and data verification. The results of this study indicate that the improvement of the memorization of the Qur'an through the Talaqqi method goes well through the planning, implementation, and evaluation processes. With the Talaqqi method, there are many students whose memorization quality increases to 80%, according to the target set by the foundation and the Ustadz. The increase in the target of memorization is because it is supported by the factor of supporting students' memorization activities, namely learning Tahsin, which is useful in developing the ability to read the Qur'an and then the support from parents, a beautiful and comfortable place for memorizing the Qur'an. In addition, there is an inhibiting factor, namely the lack of tutors for Tahfidz subjects. There is a sense of laziness in students and lack of time management.